Comparison of smoking traditional, heat not burn and electronic cigarettes on salivary cytokine, chemokine and growth factor profile in healthy young adults–pilot study - Zięba, Sara; Maciejczyk, Mateusz; Antonowicz, Bożena; Porydzaj, Aleksandra; Szuta, Mariusz; Lo Giudice, Giuseppe; Lo Giudice, Roberto; Krokosz, Stanisław; Zalewska, Anna (Frontiers in Physiology, 2024)
Objective: Smoking is the cause of numerous oral pathologies. The aim of the study was to evaluate the effect of smoking traditional cigarettes, e-cigarettes, and heat-not-burn products on the content of salivary cytokines, chemokines, and growth factors in healthy young adults.Design: Three groups of twenty-five smokers each as well as a control group matched in terms of age, gender, and oral status were enrolled in the study. In unstimulated saliva collected from study groups and participants from the control group, the concentrations of cytokines, chemokines, and growth factors were assessed by Bio-Plex® Multiplex System.Results: We demonstrated that smoking traditional cigarettes is responsible for increasing the level of IFN-γ compared to non-smokers and new smoking devices users in unstimulated saliva in the initial period of addiction. Furthermore, e-cigarettes and heat-not-burn products appear to have a similar mechanism of affecting the immune response system of unstimulated saliva, leading to inhibition of the local inflammatory response in the oral cavity. Conclusion: Smoking traditional cigarettes as well as e-cigarettes and heat-not-burn products is responsible for changes of the local immune response in saliva. Further research is necessary to fill the gap in knowledge on the effect of new smoking devices on the oral cavity immune system.